Wholesale Apocalypse: Brand Names in Margaret Atwood's Oryx and Crake. (2nd April 2016) - Grimbeek, Marinette
Abstract : Coinages pervade Margaret Atwood's post-apocalyptic novel Oryx and Crake (2003). Most of the neologisms in the novel denote corporations and their products and form part of a thoroughgoing critique of consumerism. The coinages are jarringly hyperbolic and their orthography often evokes contrary connotations. However, in the thematic context of the novel, coining practices follow certain patterns and function as effective, if ambiguous, satirical tools. On one level, the practice of branding is thoroughly satirized. On another, however, the neologisms point to both the limitations and possibilities of satire when dealing with the themes addressed in the novel: commoditization, environmental damage on a planetary scale, and a vision of the imminent end of humanity itself.